2023
DOI: 10.1111/all.15750
|View full text |Cite
|
Sign up to set email alerts
|

The step‐down approach in children with cow's milk allergy: Results of a randomized controlled trial

Abstract: BackgroundThe Step‐Down Approach for Cow's Milk Allergy (SDACMA) trial evaluated the tolerability and the rate of immune tolerance acquisition in CMA children starting dietary treatment with amino acid‐based formula (AAF) and then switching to EHCF containing the probiotic Lacticaseibacillus  rhamnosus GG (EHCF + LGG).MethodsRandomized controlled trial involving IgE‐mediated CMA children receiving AAF from at least 4 weeks. EHCF + LGG tolerance was evaluated by the results of double‐blind placebo‐controlled fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In a recent study, 60 infants younger than six months with CMA were randomized to receive a non-allergenic amino acid-based or less allergenic extensively hydrolyzed formula. Remission rates were compared at 12 months [ 7 ]. Three percent and 48% of infants in the amino acid-based and extensively hydrolyzed formula groups, respectively, achieved remission, with no severe allergic symptoms associated with the extensively hydrolyzed formula.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, 60 infants younger than six months with CMA were randomized to receive a non-allergenic amino acid-based or less allergenic extensively hydrolyzed formula. Remission rates were compared at 12 months [ 7 ]. Three percent and 48% of infants in the amino acid-based and extensively hydrolyzed formula groups, respectively, achieved remission, with no severe allergic symptoms associated with the extensively hydrolyzed formula.…”
Section: Discussionmentioning
confidence: 99%
“…After 12 months, the rate of CT was higher in the EHCF + LGG group (0.48, 95% exact CI 0.29–0.67, n /N = 14/29) than in the AAF group (0.03, 95% exact CI 0.001–0.17, n /N = 1/30). They demonstrated that in IgE-mediated CMPA children, the step-down from AAF to EHCF + LGG was well tolerated and could facilitate the immune tolerance acquisition [ 127 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the health effect of probiotics has high strain tolerance, and infants with different constitutions, different genetic backgrounds and different intestinal flora should be different, and the research on probiotics can be located on the individual strains. At present, researchers have evaluated the safety and the efficacy of EHCF with LGG by randomized, double-blind trial, and the results showed that EHCF + LGG could be tolerated by the vast majority of IgE-mediated CMA children, and that the step-down approach from AFF to EHCF + LGG could promote a faster acquisition of immune tolerance ( 119 ). Although the use of probiotics is beneficial to promote immune regulation and alleviate clinical symptoms, more methodologically based and homogenized research is needed to more specifically study each type, dose, and time of probiotic supplementation for the establishment of definitive care protocols.…”
Section: Suggestions and Prospectsmentioning
confidence: 99%